2022
DOI: 10.1186/s43014-022-00092-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chinese steamed bun and bread processing on pesticide residues in wheat flour

Abstract: The changes of five pesticides including imidacloprid, triadimefon, fenitrothion, chlorpyrifos-methyl, and chlorpyrifos in wheat flour during Chinese steamed bun and bread processing were systematically investigated. The pesticide residues were determined by high performance liquid chromatography coupled with diode array detector. Dough mixing step in both Chinese steamed bun and bread processing reduced the concentration of five pesticide residues significantly by 33 to 46%. It was mainly attributed to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…For example, malathion, an insecticide, would be easily dissipated during cake and bread baking (Alnaji et al ., 1979; Alnaji & Kadoum, 1981). To variable extents, insecticides like imidacloprid, triadimefon, fenitrothion, chlorpyrifos‐methyl, and chlorpyrifos would be reduced in steamed bread and noodles, although the latter effect was partly attributed to increased moisture content in the prepared foods (Liang et al ., 2022a, 2022b). On the contrary, based on data reported on dry basis, we have reported that glyphosate, a popular herbicide, was stable during bread production (Gélinas et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, malathion, an insecticide, would be easily dissipated during cake and bread baking (Alnaji et al ., 1979; Alnaji & Kadoum, 1981). To variable extents, insecticides like imidacloprid, triadimefon, fenitrothion, chlorpyrifos‐methyl, and chlorpyrifos would be reduced in steamed bread and noodles, although the latter effect was partly attributed to increased moisture content in the prepared foods (Liang et al ., 2022a, 2022b). On the contrary, based on data reported on dry basis, we have reported that glyphosate, a popular herbicide, was stable during bread production (Gélinas et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%